Analisis Motivasi Kerja dalam Mempengaruhi Kineja Karyawan pada Aqua Home Service Mulia Bogor - Setyawan, Joko; Juri (Lembaga Riset Penelitian dan PKM Aliansi Manajemen Indonesia, 2025)
This study aims to analyze the effect of work motivation on employee performance at Aqua Home Service Mulia Bogor. The research background is grounded in the observed low level of employee performance, which is presumed to be influenced by work motivation factors. The independent variable in this study is work motivation, while employee performance serves as the dependent variable. The sample consists of 50 respondents, selected using a census sampling technique. The research adopts a quantitative approach with an explanatory research design. Data analysis was conducted using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach and a Likert-scale measurement model. The findings indicate that work motivation has a positive and significant effect on employee performance. These results suggest that business owners and managers should pay close attention to factors that enhance employees’ work motivation, as such improvements can ultimately lead to increased performance.